Methodologies of Verbal autopsy and Social autopsy tools, adopted by VASA studies in exploring under-five mortality determinants - Siddiqui, Muhammad Bilal; Wan Ng, Chiu; Wah Yun Low (International Journal of Endorsing Health Science Research, 2018)
Background: Verbal Autopsy/Social Autopsy (VASA) tools should be based on a well-holistic conceptual framework, allowing them to record and organize a wide range of determinants and contributors of child mortality in developing countries. This paper aims to review how successfully VASA studies have been able to record and organize biological and social determinants of child mortality, in pursuit of World Health Organization’s (WHO) guidelines for verbal autopsy (VA) and Kalter’s recommendations for social autopsy (SA). Methodology: A systematic search of literature from January 1995 to January 2018 was conducted on primary studies which attempted VA and SA on deceased cases of under-5 child mortalities using VA and SA questionnaires. A thorough search revealed 16 directly relevant papers. Results: Sixteen relevant studies from 14 countries revealed the two most common conceptual frameworks which were utilized for VASA studies. VA component of three studies followed W.H.O.’s guidelines, while the SA component of the other three studies followed Kalter’s recommendations. The most robust VA tools identified were INDEPTH Network VA tool, INCLEN VA tool, and WHO VA tool; while CHERG SA tool and BASICS SA tool were found as the most robust SA tools. Conclusion: Due to the fact that only separate recommendations for VA, and conceptual frameworks for SA exists and no evidence on integrated conceptual framework exists, we suggest that there is a great need for developing a conceptual framework, based on which an integrated VASA tool can be developed and utilized in VASA based child mortality investigations in developing countries.